Traumatic Brain Injuries during Development: Implications for Alcohol Abuse - Weil, Zachary M.; Karelina, Kate (Frontiers in Behavioral Neuroscience, 2017)
Traumatic brain injuries are strongly related to alcohol intoxication as by some estimates half or more of all brain injuries involve at least one intoxicated individual. Additionally, there is mounting evidence that traumatic brain injuries can themselves serve as independent risk factors for the development of alcohol use disorders, particularly when injury occurs during juvenile or adolescent development. Here, we will review the epidemiological and experimental evidence for this phenomenon and discuss potential psychosocial mediators including attenuation of negative affect and impaired decision making as well as neurochemical mediators including disruption in the glutamatergic, GABAergic and dopaminergic signaling pathways and increases in inflammation.